PERBANDINGAN GASTRODIPLOMASI INDONESIA DAN JEPANG TERHADAP AMERIKA SERIKAT DALAM MENINGKATKAN HUBUNGAN DIPLOMATIK ANTAR NEGARA - Jovanka Rachel Ronauli (2023)
Food is a basic human need that is met every day. The existence of globalization makes the barriers that limit the country increasingly faded. Diplomacy is one of the soft power that can be used to encourage countries to be able to compete in the international arena. In establishing state relations, food can be used as a tool to achieve state interests through public diplomacy which is called gastrodiplomacy. Each country has its own special food and can be used as an attraction to attract people from other countries. The higher the interest or awareness of a country, the country will also receive benefits both in terms of the economy, tourism, and position in international forums. Gastrodiplomacy discussed in this study is a comparison of the effectiveness of activities related to culinary promotion carried out by Indonesia and Japan against the United States. It is measured using five objective keys, namely being able to understand identity, using bottom-up formulations, tactility, building relationships and the role of the diaspora. Both countries have their own uniqueness and different approaches. Indonesia is a country rich in culinary culture with a variety of tastes. Meanwhile, Japan offers traditional food that is healthy and suitable for diets. While the United States is a country inhabited by a heterogeneous society. There are several indications that make Indonesia lagging behind in terms of gastrodiplomacy, so that Japan is considered to be superior in implementing gastrodiplomacy.